Anti-microbial susceptibility pattern of infant feeding bottles from bottle fed infants - Kondapalli, Chandra Sekhar; Siddhartha, Garikapati (International Journal of Contemporary Pediatrics, 2017)
Background: Breastfeeding, which has been declining in the recent years because of advances in science. Thought the importance of breastfeeding have been studied, the implementation of the same is being difficult, because of lack of awareness among mothers, health care workers etc. Methods: Consent was taken from the parents who fed their babies with infant feeding bottle and explained about the necessity to obtain culture of the bottles and nipples. Swab was inoculated on the MacConkey agar culture. Antibiotic susceptibility testing will be done for all the isolates. Results: This study showed that 32% were initiated on bottle feeding before 6mo of age and 45% during 6-12mo of age and 23% after age of 1 yr. The most common presenting illness were diarrhea (43%) followed by respiratory illness (39%). Bottle feeding has contribution to the malnutrition and showed that adequate cleaning practices were followed by only 41 % of mothers and 9% of mothers had poor cleaning practices. The incidence of illness is 60. 7% in only top fed babies compared to babies who are both breast fed and bottle fed 39.3%. The most common isolate found was E-coli 45% (24) followed by. Kliebsella 24% (12), Staphylococcus 16% (9), CONS 9% (5), Enterobacterecciea 3% (2) and Pseudomonas 0.8% (1). 52% of the sample showed fungal isolation positive. Conclusions: The incidence of bottle feeding was found more common in working women(53%) compared to housewife(19%). Illiteracy of the family contributed to the over dilution of top milk .most common organism is E-coli.